2022
DOI: 10.3399/bjgp22x719501
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID in children and young people: uncertainty and contradictions

Abstract: AN EVOLVING PICTURE'Long COVID' describes both ongoing symptomatic COVID-19 (5-12 weeks after onset) and post-COVID-19 syndrome (≥12 weeks after onset). 1 Long COVID is also a patient-preferred term 2 so will be used throughout this editorial to describe symptoms lasting ≥4 weeks after an acute episode of COVID-19.As the phenomenon of long COVID emerged and came to be recognised, including with the publication of the guideline by the National Institute for Health and Care Excellence, Scottish Intercollegiate G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Compared to various preceding studies based on online questionnaires [ 14 ], the identification of long COVID symptoms in this study may be more accurate because the symptoms were identified by face-to-face interviews. This study is unique in that we were able to perform a direct comparison of symptoms in children with those in adults because both the adults and children were seen by the same general physicians using the same evaluation tools as those proposed from a study conducted in Britain [ 34 ]. However, our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to various preceding studies based on online questionnaires [ 14 ], the identification of long COVID symptoms in this study may be more accurate because the symptoms were identified by face-to-face interviews. This study is unique in that we were able to perform a direct comparison of symptoms in children with those in adults because both the adults and children were seen by the same general physicians using the same evaluation tools as those proposed from a study conducted in Britain [ 34 ]. However, our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in other parts of the world also attach great importance to the relationship between the physician and patient in treating long COVID, including the authors of two UK studies. 8 , 9 Atherton et al note that 'the patient–doctor relationship is vital in the management of people with long COVID' . 16 Effective communication and ongoing support through follow-up appointments are vital for rehabilitation and patient satisfaction because it was reported that only patients that were offered this type of support felt that they had received satisfactory care.…”
Section: Discussionmentioning
confidence: 99%
“… 4 National Institute for Health and Care Excellence, 5 Scottish Intercollegiate Guideline Network, 6 and the Royal College of General Practitioners 7 have established comprehensive definitions, norms, and guidelines to address the multifaceted nature of long COVID. 8 However, the reality faced by patients and medical staff is complex because of sometimes controversial clinical conditions. Above all, studies of survivors and physicians report a wide array of experiences among individuals who have been struggling with post-COVID symptoms for multiple years.…”
Section: Introductionmentioning
confidence: 99%
“…GPs have an important role in listening to CYP with long COVID, supporting them, and referring to long COVID services if available. 31 …”
Section: Discussionmentioning
confidence: 99%